2020
DOI: 10.1183/23120541.00768-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the first COVID-19 surge on severe asthma patients in the UK. Which is worse: the virus or the lockdown?

Abstract: Respiratory viral infections are a significant cause of morbidity in asthma (1). Patients with severe asthma were assumed to be at greater risk from novel coronavirus-2 (COVID-19) infection. In the global response to the COVID-19 pandemic, multiple countries enacted social containment policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Furthermore, 55% of our SA patients formally shielded according to government mandate Additionally, our SA patients were on high dose inhaled corticosteroids, namely ciclesonide which has been shown to inhibit SARS‐CoV‐2 replication in vitro and attracted interest as a potential COVID‐19 therapy 8 . Our findings for SA mortality were consistent with recently published findings from the UK Severe Asthma Registry 9 …”
Section: Pwnoa Pwa Overall P‐value N = 5724 N = 914 N = 6638 (Pwnoa Vs Pwa)supporting
confidence: 86%
“…Furthermore, 55% of our SA patients formally shielded according to government mandate Additionally, our SA patients were on high dose inhaled corticosteroids, namely ciclesonide which has been shown to inhibit SARS‐CoV‐2 replication in vitro and attracted interest as a potential COVID‐19 therapy 8 . Our findings for SA mortality were consistent with recently published findings from the UK Severe Asthma Registry 9 …”
Section: Pwnoa Pwa Overall P‐value N = 5724 N = 914 N = 6638 (Pwnoa Vs Pwa)supporting
confidence: 86%
“…A large COVID-19 hospitalized Italian population showed that patients with worse COVID-19 outcome (death/need for ventilation vs. discharge at home without requiring invasive procedures) suffered from more severe asthma (GINA 4/ 5, 43 vs. 14%, p = 0.040) [66]. Although biologic-treated patients with asthma typically present with the most severe manifestations of the disease, these studies showed that the number of COVID-19-related admissions and mortality in these patients was strikingly low [67][68][69][70][71][72][73][74]. Treatment with biologicals for severe asthma also seems to have no significant effect on the outcome of COVID- 19.…”
Section: Severe Asthma and Covid-19mentioning
confidence: 90%
“…In addition, Smith et al . [17] demonstrated worsening mental health in patients with asthma undergoing shielding during the pandemic, and individuals with a history of anxiety or depression were more vulnerable. Our study was designed in response to rapidly defined public health research priorities for people experiencing severe distress during the COVID‐19 pandemic [18,19].…”
Section: Introductionmentioning
confidence: 99%